Influence of Coating with Some Natural Based Materials on the Erosion Wear Behavior of Glass Fiber Reinforced Epoxy Resin - Aseel Basim Abdul Hussein (Al-Khwarizmi College of Engineering – University of Baghdad, 2015)
Abstract